Aspirin versus clopidogrel for chronic maintenance monotherapy after percutaneous coronary intervention (HOST-EXAM): an investigator-initiated, prospective, randomised, open-label, multicentre trial. Issue 10293 (26th June 2021) - Koo, Bon-Kwon; Kang, Jeehoon; Park, Kyung Woo; Rhee, Tae-Min; Yang, Han-Mo; Won, Ki-Bum; Rha, Seung-Woon; Bae, Jang-Whan; Lee, Nam Ho; Hur, Seung-Ho; Yoon, Junghan; Park, Tae-Ho; et al.
Summary: Background: Optimal antiplatelet monotherapy during the chronic maintenance period in patients who undergo coronary stenting is unknown. We aimed to compare head to head the efficacy and safety of aspirin and clopidogrel monotherapy in this population. Methods: We did an investigator-initiated, prospective, randomised, open-label, multicentre trial at 37 study sites in South Korea. We enrolled patients aged at least 20 years who maintained dual antiplatelet therapy without clinical events for 6–18 months after percutaneous coronary intervention with drug-eluting stents (DES). We excluded patients with any ischaemic and major bleeding complications. Patients were randomly assigned (1:1) to receive a monotherapy agent of clopidogrel 75 mg once daily or aspirin 100 mg once daily for 24 months. The primary endpoint was a composite of all-cause death, non-fatal myocardial infarction, stroke, readmission due to acute coronary syndrome, and Bleeding Academic Research Consortium (BARC) bleeding type 3 or greater, in the intention-to-treat population. This trial is registered with ClinicalTrials.gov, NCT02044250 . Findings: Between March 26, 2014, and May 29, 2018, we enrolled 5530 patients. 5438 (98·3%) patients were randomly assigned to either the clopidogrel group (2710 [49·8%]) or to the aspirin group (2728 [50·2%]). Ascertainment of the primary endpoint was completed in 5338 (98·2%) patients. During 24-month follow-up, the primary outcome occurred in 152 (5·7%) patients in the clopidogrel group and 207 (7·7%) in the aspirin group (hazard ratio 0·73 [95% CI 0·59–0·90]; p=0·0035). Interpretation: Clopidogrel monotherapy, compared with aspirin monotherapy during the chronic maintenance period after percutaneous coronary intervention with DES significantly reduced the risk of the composite of all-cause death, non-fatal myocardial infarction, stroke, readmission due to acute coronary syndrome, and BARC bleeding type 3 or greater. In patients requiring indefinite antiplatelet monotherapy after percutaneous coronary intervention, clopidogrel monotherapy was superior to aspirin monotherapy in preventing future adverse clinical events. Funding: ChongKunDang, SamJin, HanMi, DaeWoong, and the South Korea Ministry of Health and Welfare.